Grassroots Garveyism : The Universal Negro Improvement Association in the Rural South, 1920-1927 - Rolinson, Mary G. (Book collections on Project MUSE., 2007)
The black separatist movement led by Marcus Garvey has long been viewed as a phenomenon of African American organization in the urban North. But as Mary Rolinson demonstrates, the largest number of Universal Negro Improvement Association (UNIA) divisions and Garvey's most devoted and loyal followers were found in the southern Black Belt. Rolinson remaps the movement to include this vital but overlooked region, and offers a view of what southern Garveyites were like. Even after the UNIA had all but disappeared in the South in the 1930s, she says, the movement's tenets of race organization, unit.